Wetland-Based Transformational Leadership in Building the Image and Competitiveness of Primary Schools - Diani Ayu Pratiwi; Aslamiah Aslamiah (FKIP - Universitas Riau, 2026)
Primary schools located in wetland areas face ecological, social, and public perception challenges that may affect their institutional image and competitiveness. This study aims to analyze how transformational leadership contextualized to wetland characteristics contributes to building school image and enhancing the competitiveness of primary schools. Employing a descriptive qualitative research design, the study was conducted at Madrasah Diniyah Islamiah Muhammadiyah Kindaung Banjarmasin, a school situated along a riverbank. Data were collected through in-depth interviews, observations, and document analysis involving the principal, teachers, parents, and community representatives. The findings indicate that wetland-based transformational leadership is implemented through a contextual vision, ecological role modelling, cultural values, school innovation strategies, and adaptive mentoring of school members. Such leadership plays a crucial role in shaping an authentic school image and strengthening public trust, which in turn contributes to enhanced institutional competitiveness. The study concludes that transformational leadership integrated with ecological contexts can transform environmental constraints into a distinctive identity and strategic advantage for primary schools.